Piramida: Peninggalan Karya Seni Dunia dari Wilayah Barat Hingga Timur (Bagian I) - Hanny Wijaya (Humaniora, 2011)
There is a terminology that human learn from the past to reach a better future. Based on this understanding, human start to learn history. Scientists learn history from historical building and cultural heritage from the past. One of the most important buildings is pyramid. For quite a long time, many people do not know that pyramid is only a fundamental form. Everytime people hear a word ‘pyramid’, they will directly refer to Egyptian Pyramid. However, there are many different forms of pyramid and they were scattered around the world, from western to eastern countries. Besides Egypt, some countries that have been well-known about their pyramids are Mesopotamia, Egypt, Sudan, Nigeria, Greece, Spain, China, Mexico, North America, Italy, India and Indonesia. In this first part of research, it will discuss Egyptian and Mesopotamian Pyramids as the oldest western cultural heritage in the world. Hopefully, this research will enhance the knowledge about pyramids more specific and reader will be able to differentiate the function and form of each pyramid in the world.